Familiarity and distance in ethnographic fieldwork: field positions and relations in adult education. Issue 1 (2nd January 2021) - Duch, Henriette; Rasmussen, Annette
ABSTRACT: Familiarity and distance is an issue that is much discussed in ethnographic fieldwork. This paper focuses on the topic of balancing familiarity and distance when the researcher is directly or indirectly part of the field, which in the study consists of an adult education context of two different teacher-training courses for upper secondary teachers. The fieldworker is also a teacher at one of the courses in the study, which is thus in a double sense framed by the challenge of an adult education study. The analysis is based on Bourdieu's concept of participant objectification and Gold's categorising of roles in ethnographic fieldwork. It illustrates how different contexts depending on the prior familiarity of the fieldworker provide access to different degrees of participation. The particular adult education context and fieldworker relations complicate the fieldwork relations and the act of balancing familiarity and distance.